Photonic crystal hydrogel-based thermochromic intelligent window material as well as preparation method and application thereof

By combining the temperature-sensitive hydrogel with three-dimensional photonic crystal structure and introducing transparent conductive oxide nanoparticles, the shortcomings of the existing thermochromic window in temperature range and color change control are solved, and a variety of color discoloration effects and excellent infrared shielding performance are achieved.

CN119613784AActive Publication Date: 2025-03-14SOUTH CHINA UNIV OF TECH

Patent Information

Application Number
CN202411711523.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-03-14
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

Existing thermochromic windows are difficult to achieve multiple colors change control over a wide temperature range, the color change temperature range is limited, and the infrared shielding function is lacking.

Method used

The temperature-sensitive hydrogel is combined with a three-dimensional photonic crystal structure, and the phase transition temperature of the hydrogel is accurately adjusted by adjusting the ratio of the temperature-sensitive monomer and modified cellulose, and the photothermal response efficiency is improved.

Benefits of technology

It realizes multiple color discoloration effects over a wide temperature range, has good privacy protection functions and decorative effects, and at the same time improves the photothermal response efficiency under low temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119613784A_ABST
    Figure CN119613784A_ABST
Patent Text Reader

Abstract

The invention discloses a photonic crystal hydrogel-based thermochromic intelligent window material as well as a preparation method and application thereof. The photonic crystal hydrogel-based thermochromic intelligent window material is obtained by filling a three-dimensional photonic crystal structure with a temperature-sensitive hydrogel prepolymerization solution and then curing the three-dimensional photonic crystal structure; the preparation method comprises the following steps: adding a temperature-sensitive monomer, modified cellulose and a cross-linking agent into deionized water, carrying out ultrasonic dispersion, stirring under an ice bath condition until the materials are completely dissolved, adding an initiator, stirring until the materials are dissolved, adding N, N, N ', N'-tetramethylethylenediamine, and uniformly stirring to obtain the temperature-sensitive hydrogel prepolymer. The photonic crystal hydrogel-based thermochromic intelligent window material prepared by the invention can regulate and control the window transmittance in real time according to the environment temperature, and has a sensitive thermochromic effect and excellent infrared shielding performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a thermochromic material, in particular to a photonic crystal hydrogel-based thermochromic smart window material and a preparation method and application thereof, belonging to the technical field of smart thermal insulation windows. Background Art

[0002] Building energy consumption accounts for about 36% of the world's total energy consumption, of which heating, ventilation and air conditioning (HVAC) systems account for about 40-50% of building energy consumption. The windows of a building will affect the heating, cooling and lighting inside the house. Optimizing windows is an important step in reducing building energy consumption. In order to improve energy efficiency and living comfort, research on smart windows has attracted widespread attention. Smart windows can adjust the transmittance of windows according to light intensity, ambient temperature, etc., control the indoor temperature to keep it within the comfortable range for the human body, and reduce the energy consumption of the HVAC system.

[0003] The smart windows that are currently being studied more include electrochromic windows and thermochromic windows. Electrochromic windows can accurately control the transmittance and color of windows by regulating voltage, but electrochromic windows are actively regulated and require human control, and electrochromic windows require power supply, which further increases energy consumption; while thermochromic windows are passively regulated and can adaptively adjust the window transmittance according to the ambient temperature, achieving the color-changing effect without additional power supply.

[0004] Chinese invention patent CN 116284850 B provides a method for preparing an ionic hydrogel electrolyte and applying it to an electrochromic smart window. The method mixes lithium chloride and acrylamide to prepare a deep eutectic solvent, then adds the deep eutectic solvent to a hydrogel precursor solution containing N-isopropylamide, sodium dodecyl sulfate, and di-tert-butyl peroxyisopropylbenzene, fills the hydrogel precursor solution into a hollow glass interlayer composed of conductive glass containing a WO3 film, and solidifies it to obtain an electrochromic smart window. However, this technology requires additional power supply to achieve the color change effect of the window, and only relies on hydrogel to achieve electrochromism. The smart window has poor sunlight modulation ability, and the electrochromic window has higher energy consumption.

[0005] Chinese invention patent CN 114573756 B discloses a method for preparing a thermosensitive gel for use in thermochromic smart windows. This technology uses hydroxypropyl methylcellulose to modify N-isopropyl acrylamide, and obtains a poly N-isopropyl acrylamide / hydroxypropyl methylcellulose thermosensitive composite gel by redox-induced free radical polymerization at low temperature. Although the phase transition temperature of the hydrogel of this technology is close to room temperature and the thermochromic is relatively energy-saving, the thermochromic prepared only by thermosensitive monomers such as N-isopropyl acrylamide can only change from a transparent state to a white opaque state. Moreover, in winter, the thermochromic windows cannot reach the phase transition temperature of the thermosensitive monomer because the temperature is low, so the hydrogel cannot undergo a phase change, resulting in excessive light intensity in the room, which greatly reduces the living comfort in winter.

[0006] Chinese invention patent application CN 104129121 A discloses a thermochromic window, the solar transmittance of which can be adjusted according to temperature. The thermochromic window includes a flexible substrate, a thermochromic film arranged on the flexible substrate, and a substrate bonded to the thermochromic film after heat treatment. The components of the thermochromic material are selected from one of vanadium dioxide (VO2), titanium (III) oxide (Ti2O3), niobium dioxide (NbO2) and nickel sulfide (NiS). The phase change temperature of the thermochromic material is controlled by doping the thermochromic material with a dopant. The phase change temperature of the thermochromic material of this technology decreases with the increase of the doping ratio of the dopant, but the thermochromic material is a metal oxide, and the dopant selected from Mo, W, Nb, Ta, Fe, Al, Ti, Sn and Ni is also a metal, the overall color change temperature is high, and low temperature color change is difficult to control. Moreover, the inherent yellow-brown color of VO2 preferred by this technology seriously affects the aesthetics and visible light transmittance of the thermochromic window. In addition, since the phase change temperature of VO2 is too high, it is difficult for the thermochromic window to effectively regulate the sunlight transmittance in daily use scenarios.

[0007] In general, it is difficult for existing thermochromic windows to achieve control over the change of different colors within a wide temperature range. The color change temperature range is limited, the number of colors that can be changed is small, and there is a lack of infrared shielding function. Summary of the invention

[0008] In view of the problems existing in the prior art, the present invention provides a photonic crystal hydrogel-based thermochromic smart window material having infrared shielding performance, achieving color change in a wide operating temperature range, and having a variety of color change colors, and a preparation method thereof.

[0009] Another object of the present invention is to provide an application of the photonic crystal hydrogel-based thermochromic smart window material in the preparation of smart windows.

[0010] The purpose of the present invention is achieved through the following technical solutions:

[0011] A photonic crystal hydrogel-based thermochromic smart window material is obtained by filling a three-dimensional photonic crystal structure with a thermosensitive hydrogel prepolymer and then curing it; the thermosensitive hydrogel prepolymer is prepared by adding a thermosensitive monomer, modified cellulose, and a crosslinking agent to deionized water for ultrasonic dispersion, stirring until completely dissolved under ice bath conditions, then adding an initiator and stirring until dissolved, and adding N, N, N', N'-tetramethylethylenediamine and stirring evenly; the thermosensitive monomer has both a hydrophilic group and a hydrophobic group, and the LCST is -5~70 °C; the three-dimensional photonic crystal structure is obtained by adding a transparent conductive oxide nanoparticle dispersion to a colloidal crystal to obtain a modified colloidal crystal, and coating it on a carrier by a doctor blade or spin coating method; the colloidal crystal is obtained by pre-assembling the colloidal particle dispersion on the tube wall after centrifugation. After pre-assembly, the colloidal crystal will form a hierarchical light spot.

[0012] To further achieve the purpose of the present invention, preferably, the amounts of the thermosensitive monomer, crosslinking agent and initiator are 7~15 wt%, 0.05~0.1 wt% and 0.2~0.3 wt% of the mass of the thermosensitive hydrogel prepolymer liquid raw material, respectively; the mass ratio of the thermosensitive monomer to the modified cellulose is 10:1~40:1; the molar ratio of N,N,N',N'-tetramethylethylenediamine to the initiator is 2:1~1:1; the mass ratio of the three-dimensional photonic crystal structure to the thermosensitive hydrogel prepolymer liquid is 7~12:100.

[0013] Preferably, the temperature-sensitive monomer is one or more of N-isopropyl acrylamide, N-tert-butyl acrylamide, N,N-diethyl acrylamide, N-propyl acrylamide, N,N-dimethyl acrylamide, dimethylaminopropyl acrylamide, and ethoxyethoxyethyl acrylate.

[0014] Preferably, the modified cellulose is obtained by esterification or etherification of cellulose.

[0015] Preferably, the modified cellulose is one or more of methyl cellulose, carboxymethyl cellulose, hydroxypropyl cellulose, hydroxypropyl methyl cellulose, and cellulose nanofibers.

[0016] Preferably, the cross-linking agent is one or more of N,N'-methylenebisacrylamide, polyethylene glycol diacrylate, and allyl methacrylate; the initiator is one or more of ammonium persulfate, potassium persulfate, and sodium persulfate; the transparent conductive oxide nanoparticles are one or more of indium tin oxide (ITO), antimony tin oxide (ATO), and aluminum zinc oxide (AZO); the colloidal particle dispersion is prepared by dispersing colloidal particle powder in deionized water; the colloidal particles are polystyrene microspheres, polymethyl methacrylate microspheres, SiO2 microspheres, TiO2 microspheres, or ZnO2 microspheres.

[0017] Preferably, the mass fraction of the colloidal particles in the dispersion is 20-30 wt %; and the particle size of the colloidal particles is 160-280 nm.

[0018] Preferably, the curing temperature is 4-15 °C, and the curing time is 12-24 h; the stirring under ice bath conditions until completely dissolved, the addition of initiator and stirring until dissolved, the stirring involved in the addition of N, N, N', N'-tetramethylethylenediamine is magnetic stirring, and the stirring speed is 500-1000 rpm; the stirring time for adding N, N, N', N'-tetramethylethylenediamine is 30-60 s; the ultrasonic dispersion time is 60-120 min; the centrifugal speed is 4000-8000 rpm, and the centrifugal time is 40-60 min; the carrier is glass.

[0019] The method for preparing the photonic crystal hydrogel-based thermochromic smart window material comprises the following steps: (1) Centrifuging the colloidal particle dispersion until the colloidal particles are pre-assembled on the wall of the centrifuge tube to form hierarchical light spots of different colors, thereby obtaining colloidal crystals; (2) adding a transparent conductive oxide nanoparticle dispersion to the colloidal crystals in step (1), and dispersing the dispersion by ultrasonication to obtain modified colloidal crystals; (3) The modified colloidal crystals are self-assembled on the carrier by scraping or spin coating to form a periodically ordered three-dimensional photonic crystal structure; (4) adding the thermosensitive monomer, modified cellulose and crosslinking agent into deionized water, and stirring in an ice bath until the monomer is completely dissolved after ultrasonic dispersion, adding the initiator and stirring until dissolved, and then adding the catalyst N,N,N',N'-tetramethylethylenediamine and stirring evenly to obtain a thermosensitive hydrogel prepolymer solution; (5) Filling the thermosensitive hydrogel prepolymer solution of step (4) with the three-dimensional photonic crystal structure self-assembled on the carrier of step (3) and then curing it to obtain a photonic crystal hydrogel-based thermochromic smart window material.

[0020] The photonic crystal hydrogel-based thermochromic smart window material is used in the preparation of smart windows.

[0021] Compared with the existing color-changing windows, the beneficial effects of the present invention are: 1. The present invention utilizes a rapidly prepared three-dimensional photonic crystal structure in combination with a thermosensitive hydrogel to prepare a thermochromic smart window. The distance between colloidal particles in the photonic crystal hydrogel thermochromic smart window material changes in real time according to the ambient temperature, thereby achieving a variety of color-changing effects and sensitive temperature responsiveness of the thermochromic window. This improves the shortcomings of ordinary thermochromic windows that they can only change from colorless to white and have a single color-changing effect, and has good privacy protection and decorative effects.

[0022] 2. The present invention can precisely control the phase transition temperature of the thermosensitive hydrogel by adjusting the ratio of the thermosensitive monomer to the modified cellulose, so that the color change range of the thermochromic window is within the temperature range comfortable for the human body.

[0023] 3. The present invention introduces transparent conductive oxide nanoparticles for modification, which improves the disadvantage of low photothermal conversion efficiency of ordinary thermochromic windows in low temperature climates such as winter. The addition of transparent conductive oxide nanoparticles gives the thermochromic windows excellent photothermal response efficiency and near-infrared shielding performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 These are optical photographs of the three-dimensional photonic crystal structures prepared in Example 1 and Example 2.

[0025] Figure 2 This is an optical photograph of the photonic crystal hydrogel-based thermochromic smart window material prepared in Example 3.

[0026] Figure 3 This is an electron microscope image of the photonic crystal hydrogel-based thermochromic smart window material prepared in Example 3.

[0027] Figure 4 The transmittance spectra of Example 3 and Comparative Example 1 at 20°C and 40°C are compared.

[0028] Figure 5 Comparison of visible light modulation rates between Example 3 and Comparative Example 1.

[0029] Figure 6 The DSC curves of Example 3 and Example 7 are shown in FIG.

[0030] Figure 7 The heat insulation effect of Example 3 is compared with that of Comparative Example 2.

[0031] Figure 8 The solar transmittance of Example 3 and Comparative Example 2 at 20°C is compared.

[0032] Fig. 9 The optical photographs of Example 3 at 20°C and 40°C are compared.

[0033] Fig.10This is Example 3, a comparison of the simulated thermal insulation effects of ordinary glass and Low-E glass.

[0034] Fig.11 : is the reflection spectrum of Example 3 at 24°C to 32°C.

[0035] Fig.12 This is an optical photograph of Example 3 at 24°C to 40°C. DETAILED DESCRIPTION

[0036] In order to better understand the present invention, the present invention is further explained below in conjunction with the drawings and examples, but the examples do not constitute a limitation on the scope of protection of the claims of the present invention. Based on the examples, other examples obtained by those skilled in the art without making any creative work all fall within the scope of protection of the present invention.

[0037] The present invention aims at the problem that the thermochromic windows of the prior art are difficult to realize the control of the change of different colors in a wide temperature range, the color change temperature range is limited, and the color change is less. The present invention finds that the combination of three-dimensional photonic crystal structure and thermosensitive hydrogel can effectively solve the problems of the prior art, and obtains a photonic crystal hydrogel-based thermochromic smart window that can realize color change according to the ambient temperature and light intensity. In the technical measures of the present invention, the distance between the colloidal particles can change in real time according to the ambient temperature, so as to realize the multiple color change effects and sensitive temperature responsiveness of the thermochromic window, improve the shortcomings of ordinary thermochromic windows that can only change from colorless to white and have a single color change effect, realize the matching of multiple colors and temperatures, and have good privacy protection function and decorative effect.

[0038] At the same time, the thermosensitive hydrogel of the present invention is different from the thermosensitive materials of the prior art. First, the thermosensitive monomer has both hydrophilic and hydrophobic groups, and the LCST is -5~70 °C; second, the thermosensitive hydrogel material is provided with modified cellulose, and the phase transition temperature of the thermosensitive hydrogel can be adjusted by adjusting the ratio of the thermosensitive monomer to the modified cellulose, so that the obtained photonic crystal hydrogel-based thermochromic window has different color change ranges.

[0039] At the same time, in addition to the colloidal particles, the three-dimensional photonic crystal structure material of the present invention also has transparent conductive oxide nanoparticles. The present invention modifies the colloidal particles by introducing transparent conductive oxide nanoparticles, thereby giving the thermochromic window excellent photothermal response efficiency and near-infrared shielding performance, which can improve the problem of difficult and slow color change of thermochromic windows under low temperature conditions such as winter.

[0040] To this end, the present invention provides a photonic crystal hydrogel-based thermochromic smart window material, which is obtained by filling a three-dimensional photonic crystal structure with a thermosensitive hydrogel prepolymer and then solidifying it; the thermosensitive hydrogel prepolymer is prepared by adding a thermosensitive monomer, modified cellulose, and a crosslinking agent into deionized water, ultrasonically dispersing the mixture, stirring the mixture until it is completely dissolved under ice bath conditions, then adding an initiator and stirring the mixture until it is dissolved, and then adding N, N, N', N'-tetramethylethylenediamine and stirring the mixture evenly, wherein the thermosensitive monomer has both a hydrophilic group and a hydrophobic group, and the LCST is -5 to 70 ° C; the three-dimensional photonic crystal structure is prepared by coating a modified colloidal crystal obtained by adding a transparent conductive oxide nanoparticle dispersion into a colloidal crystal on a carrier by a doctor blade method or a spin coating method; the colloidal crystal is prepared by pre-assembling the colloidal particle dispersion on a tube wall after centrifugation, and a hierarchical light spot is formed after pre-assembly; the transparent conductive oxide nanoparticle dispersion is prepared by dispersing transparent conductive oxide nanoparticles in deionized water.

[0041] Therefore, the main feature of the photonic crystal hydrogel-based thermochromic smart window material of the present invention is the raw material composition of the thermosensitive hydrogel prepolymer and the three-dimensional photonic crystal structure itself. As for the amount of thermosensitive monomer, modified cellulose, crosslinking agent, N, N, N', N'-tetramethylethylenediamine in the thermosensitive hydrogel prepolymer, and the amount of colloidal particles and transparent conductive oxide nanoparticles in the three-dimensional photonic crystal structure, it can be obtained by experiment according to the purpose of the present invention. The specific selection of the thermosensitive monomer, modified cellulose, and crosslinking agent involved in the present invention can also be optimized by experiment according to the present invention. Of course, the thermosensitive monomer of the present invention is required to have both a hydrophilic group and a hydrophobic group, and the LCST is -5~70 ° C.

[0042] Example 1: Preparation of three-dimensional photonic crystal structure (1) Preparation of colloidal crystals Using soap-free emulsion polymerization, 8 g styrene, 1 g methyl methacrylate, and 100 g deionized water were added to a flask equipped with a mechanical stirrer, a thermometer, and a condenser, and heated in a water bath at 75 °C. After 30 min, 5 mL of 3% ammonium persulfate solution was added, and after 7.5 h of reaction, a carboxylated polystyrene (PS) microsphere dispersion was obtained. The PS microsphere dispersion was then centrifuged at 8000 rpm for 60 min, and the PS microspheres were preassembled at the bottom of the centrifuge tube to form PS colloidal crystals, at which time bright structural colors could be observed.

[0043] (2) Preparation of modified colloidal crystals (PS@ATO) Take 5 ml of the pre-assembled PS colloidal crystals in step (1), add 0.05 g of ATO dispersion (50 wt%), add deionized water to prepare a dispersion with a mass fraction of 20 wt%, and after ultrasonic dispersion for 60 minutes, obtain modified colloidal crystals (PS@ATO).

[0044] (3) Preparation of three-dimensional photonic crystal structures

[0045] The modified colloidal crystals were scraped onto a glass sheet of 100 mm*100 mm*1 mm using a four-sided preparation apparatus with a scraping thickness of 25 μm. After self-assembly, a three-dimensional photonic crystal structure with no cracks and uniform structural color was obtained.

[0046] Example 2: Preparation of three-dimensional photonic crystal structure

[0047] (1) Preparation of colloidal crystals

[0048] Using soap-free emulsion polymerization, 8 g styrene, 1 g methyl methacrylate, and 100 g deionized water were added to a flask equipped with a mechanical stirrer, a thermometer, and a condenser, and heated in a water bath at 75 °C. After 30 min, 5 mL of 3% ammonium persulfate solution was added, and after 7.5 h of reaction, a carboxylated polystyrene (PS) microsphere dispersion was obtained. The PS microsphere dispersion was then centrifuged at 8000 rpm for 60 min, and the PS microspheres were preassembled at the bottom of the centrifuge tube to form PS colloidal crystals, at which time bright structural colors could be observed.

[0049] (2) Preparation of modified colloidal crystals (PS@ATO)

[0050] Take 5 ml of the pre-assembled PS colloidal crystals in step (1), add 0.05 g of ATO dispersion (50 wt%), add an appropriate amount of deionized water to prepare a dispersion with a mass fraction of 25 wt%, and after ultrasonic dispersion for 60 minutes, obtain modified colloidal crystals (PS@ATO).

[0051] (3) Preparation of three-dimensional photonic crystal structures

[0052] The modified colloidal crystals were scraped onto a glass sheet of 100 mm*100 mm*1 mm using a four-sided preparation apparatus with a scraping thickness of 25 μm. After self-assembly, a three-dimensional photonic crystal structure with no cracks and uniform structural color was obtained.

[0053] Figure 1The optical photographs of the three-dimensional photonic crystal structures of Example 1 and Example 2 show that the modified colloidal crystals with a mass fraction of 20 wt% and 25 wt% can be quickly prepared by scraping to form a three-dimensional photonic crystal structure without cracks, uniform structural color, and high contrast. This is because when the mass fraction of the modified colloidal crystal is higher than the critical mass fraction, the microspheres in the colloidal crystal will be partially preassembled, and a uniform three-dimensional photonic crystal structure can be quickly obtained by scraping, which improves the problem of low efficiency in preparing three-dimensional photonic crystal structures by the "drip coating method".

[0054] Example 3: Preparation of photonic crystal hydrogel-based thermochromic smart window materials

[0055] (1) Preparation of colloidal crystals

[0056] Using soap-free emulsion polymerization, 8 g styrene, 1 g methyl methacrylate, and 100 g deionized water were added to a flask equipped with a mechanical stirrer, a thermometer, and a condenser, and heated in a water bath at 75 °C. After 30 min, 5 mL of 3% ammonium persulfate solution was added, and after 7.5 h of reaction, a carboxylated polystyrene (PS) microsphere dispersion was obtained. The PS microsphere dispersion was then centrifuged at 6000 rpm for 40 min, and the PS microspheres were preassembled at the bottom of the centrifuge tube to form PS colloidal crystals, at which time bright structural colors could be observed.

[0057] (2) Preparation of modified colloidal crystals (PS@ATO)

[0058] Take 5 ml of the pre-assembled PS colloidal crystals in step (1), add 0.15 g of ATO dispersion (50 wt%), add an appropriate amount of deionized water to prepare a dispersion with a mass fraction of 25 wt%, and after ultrasonic dispersion for 60 minutes, obtain modified colloidal crystals (PS@ATO).

[0059] (3) Preparation of three-dimensional photonic crystal structures

[0060] The modified colloidal crystals were scraped onto a glass sheet of 100 mm*100 mm*1 mm using a four-sided preparation apparatus with a scraping thickness of 25 μm. After self-assembly, a three-dimensional photonic crystal structure with no cracks and uniform structural color was obtained.

[0061] (4) Preparation of photonic crystal hydrogel-based thermochromic smart window materials

[0062] 1 g of N-isopropylacrylamide, 0.03 g of carboxymethyl cellulose and 0.01 g of N, N'-methylenebisacrylamide were dissolved in 10 g of deionized water, and then magnetically stirred for 30 min in an ice bath after ultrasonic dispersion. Then 0.025 g of ammonium persulfate was added to the above solution and magnetically stirred for 10 min. Finally, 25 μl of N, N, N', N'-tetramethylethylenediamine was added and magnetically stirred for 30 s to obtain a thermosensitive hydrogel prepolymer solution. Then the hydrogel prepolymer solution was quickly poured into a hollow glass mold prepared by sandwiching a silicone frame between a glass sheet with a three-dimensional photonic crystal structure deposited and a blank glass sheet, and then the glass mold was sealed with a sealant. The glass mold was placed at 4 °C for reaction for 24 h to prepare a photonic crystal hydrogel-based thermochromic smart window material.

[0063] Figure 2 This is an optical photograph of the photonic crystal hydrogel-based thermochromic smart window material prepared in Example 3. It can be seen from the figure that the structural color of the smart window material is uniform. Figure 3 This is an electron microscope image of the photonic crystal hydrogel-based thermochromic smart window material of Example 3. It can be seen from the figure that the hydrogel wraps the PS microspheres and fills the gaps between the PS microspheres. The arrangement of the PS microspheres still maintains an ordered three-dimensional photonic crystal structure. This structural order is the source of the structural color of the thermochromic smart window material.

[0064] Example 4: Preparation of photonic crystal hydrogel-based thermochromic smart window materials

[0065] (1) Preparation of colloidal crystals

[0066] Using soap-free emulsion polymerization, 9 g styrene, 1 g methyl methacrylate, and 100 g deionized water were added to a flask equipped with a mechanical stirrer, a thermometer, and a condenser, and heated in a water bath at 75 °C. After 30 min, 5 mL of 3% ammonium persulfate solution was added, and after 7.5 h of reaction, a carboxylated polystyrene (PS) microsphere dispersion was obtained. The PS microsphere dispersion was then centrifuged at 4000 rpm for 60 min, and the PS microspheres were preassembled at the bottom of the centrifuge tube to form PS colloidal crystals, at which time bright structural colors could be observed.

[0067] (2) Preparation of modified colloidal crystals (PS@ATO)

[0068] Take 5 ml of the pre-assembled PS colloidal crystals in step (1), add 0.1 g of ATO dispersion (50 wt%), add an appropriate amount of deionized water to prepare a dispersion with a mass fraction of 30 wt%, and after ultrasonic dispersion for 120 min, obtain modified colloidal crystals (PS@ATO).

[0069] (3) Preparation of three-dimensional photonic crystal structures

[0070] The modified colloidal crystals were scraped onto a glass sheet of 100 mm*100 mm*1 mm using a four-sided preparation apparatus with a scraping thickness of 25 μm. After self-assembly, a three-dimensional photonic crystal structure with no cracks and uniform structural color was obtained.

[0071] (4) Preparation of photonic crystal hydrogel-based thermochromic smart window materials

[0072] 1.5 g N-isopropylacrylamide, 0.1 g carboxymethyl cellulose and 0.01 g polyethylene glycol diacrylate were dissolved in 10 g deionized water, and then magnetically stirred for 30 min in an ice bath after ultrasonic dispersion. Then 0.025 g sodium persulfate was added to the above solution and magnetically stirred for 10 min. Finally, 25 μl N, N, N', N'-tetramethylethylenediamine was added and magnetically stirred for 30 s to obtain a thermosensitive hydrogel prepolymer solution. Then the hydrogel prepolymer solution was quickly poured into a hollow glass mold prepared by sandwiching a silicone frame between a glass sheet with a three-dimensional photonic crystal structure deposited and a blank glass sheet, and then the glass mold was sealed with a sealant. The glass mold was placed at 4 °C for reaction for 24 h to prepare a photonic crystal hydrogel-based thermochromic smart window material.

[0073] Example 5: Preparation of photonic crystal hydrogel-based thermochromic smart window materials (1) Preparation of colloidal crystals Using soap-free emulsion polymerization, 11 g styrene, 1 g methyl methacrylate, and 100 g deionized water were added to a flask equipped with a mechanical stirrer, a thermometer, and a condenser, and heated in a water bath at 75 °C. After 30 min, 5 mL of 3% ammonium persulfate solution was added, and after 7.5 h of reaction, a carboxylated polystyrene (PS) microsphere dispersion was obtained. The PS microsphere dispersion was then centrifuged at 8000 rpm for 40 min, and the PS microspheres were preassembled at the bottom of the centrifuge tube to form PS colloidal crystals, at which time bright structural colors could be observed.

[0074] (2) Preparation of modified colloidal crystals (PS@ATO) Take 5 ml of the pre-assembled PS colloidal crystals in step (1), add 0.05 g of ATO dispersion (50 wt%), add an appropriate amount of deionized water to prepare a dispersion with a mass fraction of 25 wt%, and after ultrasonic dispersion for 60 minutes, obtain modified colloidal crystals (PS@ATO).

[0075] (3) Preparation of three-dimensional photonic crystal structures The modified colloidal crystals were scraped onto a glass sheet of 100 mm*100 mm*1 mm using a four-sided preparation apparatus with a scraping thickness of 25 μm. After self-assembly, a three-dimensional photonic crystal structure with no cracks and uniform structural color was obtained.

[0076] (4) Preparation of photonic crystal hydrogel-based thermochromic smart window materials 1 g of N-isopropylacrylamide, 0.06 g of carboxymethyl cellulose and 0.005 g of allyl methacrylate were dissolved in 10 g of deionized water, and then magnetically stirred for 30 min in an ice bath after ultrasonic dispersion. Then 0.02 g of potassium persulfate was added to the above solution and magnetically stirred for 10 min. Finally, 25 μl of N, N, N', N'-tetramethylethylenediamine was added and magnetically stirred for 30 s to obtain a thermosensitive hydrogel prepolymer solution. Then the hydrogel prepolymer solution was quickly poured into a hollow glass mold prepared by sandwiching a silicone frame between a glass sheet with a three-dimensional photonic crystal structure deposited and a blank glass sheet, and then the glass mold was sealed with a sealant. The glass mold was placed at 4 °C for reaction for 24 h to prepare a photonic crystal hydrogel-based thermochromic smart window material.

[0077] Example 6: Preparation of photonic crystal hydrogel-based thermochromic smart window materials (1) Preparation of colloidal crystals Using soap-free emulsion polymerization, 12 g styrene, 1 g methyl methacrylate, and 100 g deionized water were added to a flask equipped with a mechanical stirrer, a thermometer, and a condenser, and heated in a water bath at 75 °C. After 30 min, 5 mL of 3% ammonium persulfate solution was added, and after 7.5 h of reaction, a carboxylated polystyrene (PS) microsphere dispersion was obtained. The PS microsphere dispersion was then centrifuged at 6000 rpm for 40 min, and the PS microspheres were preassembled at the bottom of the centrifuge tube to form PS colloidal crystals, at which time bright structural colors could be observed.

[0078] (2) Preparation of modified colloidal crystals (PS@ATO) Take 5 ml of the pre-assembled PS colloidal crystals in step (1), add 0.15 g of ATO dispersion (50 wt%), add an appropriate amount of deionized water to prepare a dispersion with a mass fraction of 25 wt%, and after ultrasonic dispersion for 60 minutes, obtain modified colloidal crystals (PS@ATO).

[0079] (3) Preparation of three-dimensional photonic crystal structures The modified colloidal crystals were scraped onto a glass sheet of 100 mm*100 mm*1 mm using a four-sided preparation apparatus with a scraping thickness of 25 μm. After self-assembly, a three-dimensional photonic crystal structure with no cracks and uniform structural color was obtained.

[0080] (4) Preparation of photonic crystal hydrogel-based thermochromic smart window materials 1 g of N-isopropylacrylamide, 0.09 g of carboxymethyl cellulose and 0.01 g of N, N'-methylenebisacrylamide were dissolved in 10 g of deionized water, and then magnetically stirred for 30 min in an ice bath after ultrasonic dispersion. Then 0.02 g of ammonium persulfate was added to the above solution and magnetically stirred for 10 min. Finally, 25 μl of N, N, N', N'-tetramethylethylenediamine was added and magnetically stirred for 30 s to obtain a thermosensitive hydrogel prepolymer solution. Then the hydrogel prepolymer solution was quickly poured into a hollow glass mold prepared by sandwiching a silicone frame between a glass sheet with a three-dimensional photonic crystal structure deposited and a blank glass sheet, and then the glass mold was sealed with a sealant. The glass mold was placed at 4 °C for reaction for 24 h to prepare a photonic crystal hydrogel-based thermochromic smart window material.

[0081] The color of the photonic crystal hydrogel-based thermochromic smart window material can be adjusted by synthesizing colloidal particles of different particle sizes. The particle sizes of the colloidal particles synthesized in Examples 3 to 6 were tested using a Malvern Zetasizer Nano S, and the test results are shown in Table 1. It can be seen from Table 1 that as the particle size of the colloidal particles used increases, the color of the photonic crystal hydrogel-based thermochromic smart window material changes from blue to green, yellow and red. This is because the interplanar spacing of the three-dimensional photonic crystal structure self-assembled by different colloidal particles is different. As the particle size of the colloidal particles increases, the interplanar spacing of the three-dimensional photonic crystal structure increases, and its reflection peak increases accordingly, and the structural color displayed also changes.

[0082] Table 1 Example 3 Example 4 Example 5 Example 6 Colloidal particle size (nm) 180 210 225 245 Color of photonic crystal hydrogel-based thermochromic smart window materials blue green yellow red

[0083] Example 7: Preparation of photonic crystal hydrogel-based thermochromic smart window materials (1) Preparation of colloidal crystals Using soap-free emulsion polymerization, 8 g styrene, 1 g methyl methacrylate, and 100 g deionized water were added to a flask equipped with a mechanical stirrer, a thermometer, and a condenser, and heated in a water bath at 75 °C. After 30 min, 5 mL of 3% ammonium persulfate solution was added, and after 7.5 h of reaction, a carboxylated polystyrene (PS) microsphere dispersion was obtained. The PS microsphere dispersion was then centrifuged at 8000 rpm for 60 min, and the PS microspheres were preassembled at the bottom of the centrifuge tube to form PS colloidal crystals, at which time bright structural colors could be observed.

[0084] (2) Preparation of modified colloidal crystals (PS@ATO) Take 5 ml of the pre-assembled PS colloidal crystals in step (1), add 0.05 g of ATO dispersion (50 wt%), add an appropriate amount of deionized water to prepare a dispersion with a mass fraction of 25 wt%, and after ultrasonic dispersion for 60 minutes, obtain modified colloidal crystals (PS@ATO).

[0085] (3) Preparation of three-dimensional photonic crystal structures The modified colloidal crystals were scraped onto a glass sheet of 100 mm*100 mm*1 mm using a four-sided preparation apparatus with a scraping thickness of 25 μm. After self-assembly, a three-dimensional photonic crystal structure with no cracks and uniform structural color was obtained.

[0086] (4) Preparation of photonic crystal hydrogel-based thermochromic smart window materials 1 g of N-isopropylacrylamide, 0.09 g of carboxymethyl cellulose and 0.01 g of N, N'-methylenebisacrylamide were dissolved in 10 g of deionized water, and then magnetically stirred for 30 min in an ice bath after ultrasonic dispersion. Then 0.025 g of ammonium persulfate was added to the above solution and magnetically stirred for 10 min. Finally, 25 μl of N, N, N', N'-tetramethylethylenediamine was added and magnetically stirred for 30 s to obtain a thermosensitive hydrogel prepolymer solution. Then the hydrogel prepolymer solution was quickly poured into a hollow glass mold prepared by sandwiching a silicone frame between a glass sheet with a three-dimensional photonic crystal structure deposited and a blank glass sheet, and then the glass mold was sealed with a sealant. The glass mold was placed at 4°C for reaction for 24 h to prepare a photonic crystal hydrogel-based thermochromic smart window material.

[0087] Example 8: Preparation of photonic crystal hydrogel-based thermochromic smart window materials (1) Preparation of colloidal crystals The Stober method was used to prepare a monodisperse SiO2 microsphere dispersion. The SiO2 microsphere dispersion was then centrifuged at 8000 rpm for 60 min, and the SiO2 microspheres were preassembled at the bottom of the centrifuge tube to form SiO2 colloidal crystals, at which time bright structural colors could be observed.

[0088] (2) Preparation of modified colloidal crystals (SiO2@ITO) Take 5 ml of the pre-assembled SiO2 colloidal crystals in step (1), add 0.1 g of ITO dispersion (50 wt%), add an appropriate amount of deionized water to prepare a dispersion with a mass fraction of 25 wt%, and after ultrasonic dispersion for 120 min, obtain modified colloidal crystals (SiO2@ITO).

[0089] (3) Preparation of three-dimensional photonic crystal structures The modified colloidal crystals were scraped onto a glass sheet of 100 mm*100 mm*1 mm using a four-sided preparation apparatus with a scraping thickness of 25 μm. After self-assembly, a three-dimensional photonic crystal structure with no cracks and uniform structural color was obtained.

[0090] (4) Preparation of photonic crystal hydrogel-based thermochromic smart window materials 1 g N-isopropyl acrylamide, 0.01 g N-tert-butyl acrylamide, 0.03 g carboxymethyl cellulose and 0.01 g N, N'-methylenebisacrylamide were dissolved in 10 g deionized water, and then magnetically stirred for 30 min in an ice bath after ultrasonic dispersion. Then 0.025 g ammonium persulfate was added to the above solution and magnetically stirred for 10 min. Finally, 25 μl N, N, N', N'-tetramethylethylenediamine was added and magnetically stirred for 30 s to obtain a thermosensitive hydrogel prepolymer solution. Then the hydrogel prepolymer solution was quickly poured into a hollow glass mold prepared by sandwiching a silicone frame between a glass sheet with a three-dimensional photonic crystal structure deposited and a blank glass sheet, and then the glass mold was sealed with a sealant. The glass mold was placed at 15°C for reaction for 24 h to prepare a photonic crystal hydrogel-based thermochromic smart window material.

[0091] Example 9: Preparation of photonic crystal hydrogel-based thermochromic smart window materials (1) Preparation of colloidal crystals The Stober method was used to prepare a monodisperse SiO2 microsphere dispersion. The SiO2 microsphere dispersion was then centrifuged at 8000 rpm for 60 min, and the SiO2 microspheres were preassembled at the bottom of the centrifuge tube to form SiO2 colloidal crystals, at which time bright structural colors could be observed.

[0092] (2) Preparation of modified colloidal crystals (SiO2@ITO) Take 5 ml of the pre-assembled SiO2 colloidal crystals in step (1), add 0.1 g of ITO dispersion (50 wt%), add an appropriate amount of deionized water to prepare a dispersion with a mass fraction of 25 wt%, and after ultrasonic dispersion for 120 min, obtain modified colloidal crystals (SiO2@ITO).

[0093] (3) Preparation of three-dimensional photonic crystal structures The modified colloidal crystals were scraped onto a glass sheet of 100 mm*100 mm*1 mm using a four-sided preparation apparatus with a scraping thickness of 25 μm. After self-assembly, a three-dimensional photonic crystal structure with no cracks and uniform structural color was obtained.

[0094] (4) Preparation of photonic crystal hydrogel-based thermochromic smart window materials 1 g of N-isopropyl acrylamide, 0.5 g of ethoxyethoxyethyl acrylate, 0.06 g of cellulose nanofibers and 0.01 g of N, N'-methylenebisacrylamide were dissolved in 10 g of deionized water, and then magnetically stirred for 30 min in an ice bath after ultrasonic dispersion. Then 0.025 g of ammonium persulfate was added to the above solution and magnetically stirred for 10 min. Finally, 25 μl of N, N, N', N'-tetramethylethylenediamine was added and magnetically stirred for 30 s to obtain a thermosensitive hydrogel prepolymer solution. Then the hydrogel prepolymer solution was quickly poured into a hollow glass mold prepared by sandwiching a silicone frame between a glass sheet with a three-dimensional photonic crystal structure deposited and a blank glass sheet, and then the glass mold was sealed with a sealant. The glass mold was placed at 15°C for reaction for 24 h to prepare a photonic crystal hydrogel-based thermochromic smart window material.

[0095] Comparative Example 1 Comparative Example 1 is substantially the same as Example 3, except that no modified cellulose is added during the preparation of Comparative Example 1, and the remaining steps and process conditions are the same as those of Example 3.

[0096] 1 g of N-isopropylacrylamide and 0.01 g of N, N'-methylenebisacrylamide were dissolved in 10 g of deionized water, and after ultrasonic dispersion, magnetic stirring was performed in an ice bath for 30 min. Then, 0.025 g of ammonium persulfate was added to the above solution and magnetic stirring was performed for 10 min. Finally, 25 μl of N, N, N', N'-tetramethylethylenediamine was added and magnetic stirring was performed for 30 s to obtain a thermosensitive hydrogel prepolymer solution. Then, the hydrogel prepolymer solution was quickly poured into a hollow glass mold prepared by sandwiching a silicone frame between a glass sheet with a three-dimensional photonic crystal structure deposited and a blank glass sheet, and then the glass mold was sealed with a sealant on all sides and placed at 4°C for reaction for 24 h.

[0097] Figure 4 The transmittance spectra of Example 3 and Comparative Example 1 at 20°C and 40°C are shown in the figure. It can be seen from the figure that the addition of carboxymethyl cellulose can improve the transmittance of the thermochromic smart window, and Figure 5 It can be seen that carboxymethyl cellulose can improve the visible light modulation rate of thermochromic smart windows.

[0098] Comparative Example 2 Comparative Example 2 is basically the same as Example 3, except that the three-dimensional photonic crystal structure used in Comparative Example 2 is not modified by transparent conductive oxide nanoparticles, and the remaining steps and process conditions are the same as those in Example 3.

[0099] The unmodified PS colloidal crystals were scraped onto a glass sheet of 100 mm*100 mm*1 mm using a BGD four-sided preparation apparatus with a scraping thickness of 25 μm. After self-assembly, a PS photonic crystal template was obtained.

[0100] 1 g of N-isopropylacrylamide, 0.03 g of carboxymethylcellulose and 0.01 g of N, N'-methylenebisacrylamide were dissolved in 10 g of deionized water, and then magnetically stirred for 30 min in an ice bath after ultrasonic dispersion. Then 0.025 g of ammonium persulfate was added to the above solution and magnetically stirred for 10 min. Finally, 25 μl of N, N, N', N'-tetramethylethylenediamine was added and magnetically stirred for 30 s to obtain a thermosensitive hydrogel prepolymer solution. Then the hydrogel prepolymer solution was quickly poured into a hollow glass mold prepared by sandwiching a silicone frame between a glass sheet with a three-dimensional photonic crystal structure deposited and a blank glass sheet, and then the glass mold was sealed with a sealant on all sides and placed at 4°C for reaction for 24 h.

[0101] Comparative Example 3 Comparative Example 3 is basically the same as Example 3, except that the hollow glass mold used in the preparation process of Comparative Example 3 does not contain a three-dimensional photonic crystal structure, but is a mold composed of two pieces of ordinary glass, and the remaining steps and process conditions are the same as Example 3.

[0102] 1 g N-isopropylacrylamide, 0.03 g carboxymethylcellulose and 0.01 g N, N'-methylenebisacrylamide were dissolved in 10 g deionized water, and then magnetically stirred for 30 min in an ice bath after ultrasonic dispersion. Then 0.025 g ammonium persulfate was added to the above solution and magnetically stirred for 10 min. Finally, 25 μl N, N, N', N'-tetramethylethylenediamine was added and magnetically stirred for 30 s to obtain a thermosensitive hydrogel prepolymer solution. Then the hydrogel prepolymer solution was quickly poured into a hollow glass mold prepared by sandwiching a silicone frame between two blank glass sheets, and then the glass mold was sealed with a sealant on all sides, and the glass mold was placed at 4°C for reaction for 24 h.

[0103] The embodiment of the present invention uses a differential scanning calorimeter (DSC250) to measure the phase transition temperature (LCST) of the thermosensitive hydrogel, the heating rate is 1 ° C / min, the test temperature range is 25 ° C ~ 50 ° C, the protective gas and the purge gas are N2, and the flow rate is 60 mL / min.

[0104] In the present embodiment, a UV-Vis-NIR spectrophotometer (Lambda 1050+) was used to measure the transmittance spectra of the thermosensitive hydrogel at 20 °C and 40 °C, and the transmittances of different bands (visible light band 380-780 nm, sunlight band 280-2500 nm) were obtained by calculation. The calculation method is shown in formulas (1), (2), (3) and (4): in is the transmittance spectrum measured in the experiment, is the standard luminous efficiency function for human vision, is the solar irradiance spectrum for an atmospheric mass of AM 1.5. is the visible light transmittance (380~780 nm band), It is the solar transmittance (280~2500 nm band).

[0105] The embodiment of the present invention uses a temperature measuring box to test the thermal insulation effect of different windows. The size of the temperature measuring box is 20cm*20cm*15cm, and the outside of the temperature measuring box is surrounded by aluminum foil.

[0106] Figure 6The DSC curves of Example 3 and Example 7 show that the phase transition temperature of the hydrogel can be adjusted from 34.84°C to 35.51°C by adjusting the ratio of N-isopropylacrylamide to modified cellulose, indicating that the phase transition temperature of the photonic crystal hydrogel-based thermochromic window material can be precisely controlled by adjusting the ratio of the temperature-sensitive monomer to the modified cellulose, so that residents can choose the "temperature-controlled color change range" of the thermochromic window according to their own needs.

[0107] Figure 7 The figure is a comparison of the heat insulation effect of Example 3 and Comparative Example 2. It can be seen from the figure that after the temperature measuring box in Example 3 was continuously irradiated by the xenon lamp for 60 minutes, the internal temperature of the temperature measuring box was always maintained below 35.6 °C, which is within the temperature range suitable for the human body. The internal temperature of the temperature measuring box in Comparative Example 2 reached 37.8 °C at the highest point, which has exceeded the body temperature of the human body and will make people feel stuffy. The temperature difference between the temperature measuring boxes in Example 3 and Comparative Example 2 reached 3.4 °C at the highest point, indicating that transparent conductive oxide nanoparticles can improve the light-to-heat conversion efficiency of thermochromic smart windows. Figure 8 The solar transmittance of Example 3 is compared with that of Comparative Example 2. The solar transmittance of Example 3 is as low as 37%, while the solar transmittance of Comparative Example 2 is as high as 58%. In summary, it is shown that the photonic crystal hydrogel-based thermochromic window material after transparent conductive oxide nanoparticles has excellent thermal insulation and infrared shielding properties, which can keep the indoor temperature of the house at a livable temperature, thereby effectively reducing the energy consumption of the HVAC system.

[0108] Fig. 9 The optical photos of the smart window of Example 3 at 20°C and 40°C show that the smart window has good transmittance at 20°C, and becomes opaque at 40°C due to the phase change of the hydrogel, thereby blocking sunlight. The thermochromic smart window can maintain good transmittance at low temperatures and adaptively become opaque at high temperatures, indicating its application potential in the field of smart thermal insulation.

[0109] Fig.10The simulated heat insulation effect comparison of the smart window of Example 3, ordinary glass and Low-E glass (5+9A+5, the thickness of the front and rear glass is 5mm, and the thickness of the hollow interlayer is 9 mm) is shown. The center temperature of the temperature measuring box of the smart window of Example 3 reaches 40.8 °C, while the center temperatures of the temperature measuring boxes of ordinary glass and Low-E glass reach 45.7 °C and 44.9 °C respectively. At 10:00, the smart window of Example 3 can effectively block the direct sunlight due to the phase change, so the center temperature of the temperature measuring box of Example 3 is always kept at a low level. At 11:10, the temperature difference between the temperature measuring box where the smart window of Example 3 and ordinary glass and Low-E glass are located is the largest, and the cooling effect can reach 7.2 °C and 5.1 °C respectively, indicating that the photonic crystal hydrogel-based thermochromic material has excellent performance in regulating indoor temperature and energy saving, and solves the shortcomings of insufficient heat insulation effect of traditional glass and commercially available heat-insulating glass.

[0110] Fig.11 This is the reflection spectrum of the smart window of Example 3 at 24°C to 32°C. It can be seen that the reflection peak of the thermochromic smart window red-shifts as the temperature increases, indicating an increase in the interplanar spacing of the photonic crystal.

[0111] Fig.12 The optical photos of the thermochromic smart window of Example 3 at different temperatures are shown in Figure 2. At 24°C to 32°C, the volume of the hydrogel swells or shrinks with the change of temperature, causing the interplanar spacing of the photonic crystal structure to change, and the structural color of the photonic crystal also changes accordingly, achieving the effect of adaptively changing the color of the thermochromic smart window with the change of ambient temperature. At 40°C, the PNIPAm polymer chain becomes a collapsed "spherical shape", and the scattering ability of visible light is enhanced, so it becomes opaque.

[0112] Table 2 compares the optical colors of the photonic crystal hydrogel-based thermochromic smart window of Example 3 and the conventional thermochromic window of Comparative Example 3 at different temperatures. Compared with the conventional thermochromic window which can only change between colorless and white, the photonic crystal hydrogel-based thermochromic smart window can change the color of the window according to the slight temperature change, which is more accurate and sensitive. By observing the change of the window color, the occupant can intuitively feel the change of the indoor temperature, and the diversity of the window color change has good anti-privacy and decorative effects. The adaptive transmittance change of the photonic crystal hydrogel-based thermochromic smart window can provide excellent heat insulation effect.

[0113] Table 2 Temperature (°C) 24 26 28 30 32 40 Example 3 Optical Color green Yellow Green Yellow Green Orange red White Comparative Example 3 Optical Color Colorless and transparent Colorless and transparent Colorless and transparent Slightly white Partial whitening White

[0114] The phase transition temperature of the thermosensitive hydrogel can be adjusted by adjusting the ratio of the thermosensitive monomer to the modified cellulose, and the obtained photonic crystal hydrogel-based thermochromic window therefore has different color change intervals. In Example 8, the hydrophobicity of the thermosensitive hydrogel as a whole is increased by adding N-tert-butyl acrylamide, and the phase transition temperature of the hydrogel is reduced. It can be seen from Table 3 that Example 8 achieves color change at a lower temperature than Example 3, and it has completely turned red at 30 ° C, and phase change is achieved at 36 ° C. In Example 9, the hydrophilicity of the hydrogel as a whole is increased by adding the hydrophilic monomer ethoxyethoxyethyl acrylate and cellulose nanofibers, and the phase transition temperature of the hydrogel increases. It can be seen from the results of Table 4 that Example 9 needs to be at a higher temperature to achieve the change of window color, and the temperature needs to reach 42 ° C to achieve phase change. Photonic crystal hydrogel-based thermochromic windows that achieve color change in different temperature ranges can be obtained by adjusting the ratio of the thermosensitive monomer to the modified cellulose, and residents can choose according to their own needs.

[0115] Table 3

[0116] Table 4

[0117] Compared with the electrochromic window in the Chinese invention patent CN 116284850 B, the photonic crystal hydrogel-based thermochromic window of the present invention can adaptively adjust the transmittance and color change of the window according to the change of ambient temperature, without the need for additional power supply, and has lower energy consumption. Moreover, since the photonic crystal hydrogel-based thermochromic window combines a photonic crystal structure with structural color on the basis of the temperature-sensitive hydrogel, the thermochromic window of the present invention has more diverse window color change effects than the ordinary thermochromic window in CN 114573756 B, has the functions of temperature indication and privacy protection, and its practicality is significantly enhanced.

[0118] Chinese invention patent application CN104129121A utilizes metal oxides such as VO2 to prepare thermochromic windows. Compared with this, the present invention has a lower phase transition temperature range, can achieve the thermochromic effect at a lower temperature, and avoids the influence of the inherent color of metal oxides on the aesthetics of the thermochromic windows.

[0119] In summary, the present invention combines the photonic crystal structure with the thermosensitive hydrogel to obtain a smart window whose window color can change adaptively with temperature, which makes up for the shortcoming of the single color change effect of ordinary thermochromic windows. In addition, after the introduction of transparent conductive oxide nanoparticles combined with the thermosensitive hydrogel, the thermochromic window is endowed with excellent infrared shielding performance, which improves the problem that the thermochromic windows in the past were difficult and slow to change color under low temperature conditions such as winter.

[0120] It should be noted that the implementation mode of the present invention is not limited to the above-mentioned embodiments. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements. These changes and improvements all fall within the protection scope of the present invention. The protection scope of the present invention is defined by the claims.

Claims

1. A photonic crystal hydrogel-based thermochromic smart window material, characterized in that: The three-dimensional photonic crystal structure is filled with a thermosensitive hydrogel prepolymer and then solidified; the thermosensitive hydrogel prepolymer is prepared by adding a thermosensitive monomer, modified cellulose, and a cross-linking agent into deionized water, ultrasonically dispersing the prepolymer, stirring the prepolymer in an ice bath until completely dissolved, then adding an initiator and stirring the prepolymer until dissolved, and then adding N, N, N', N'-tetramethylethylenediamine and stirring the prepolymer uniformly; the thermosensitive monomer has both a hydrophilic group and a hydrophobic group, and the LCST is -5~70 °C; the three-dimensional photonic crystal structure is prepared by coating a modified colloidal crystal obtained by adding a transparent conductive oxide nanoparticle dispersion into a colloidal crystal on a carrier by a scraping method or a spin coating method; the colloidal crystal is prepared by pre-assembling the colloidal particle dispersion on the tube wall after centrifugation.

2. The photonic crystal hydrogel-based thermochromic smart window material according to claim 1, characterized in that: The amounts of the thermosensitive monomer, crosslinking agent and initiator are 7-15 wt%, 0.05-0.1 wt% and 0.2-0.3 wt% of the raw material mass of the thermosensitive hydrogel prepolymer respectively; the mass ratio of the thermosensitive monomer to the modified cellulose is 10:1-40:1; the molar ratio of N,N,N',N'-tetramethylethylenediamine to the initiator is 2:1-1:1; the mass ratio of the three-dimensional photonic crystal structure to the thermosensitive hydrogel prepolymer is 7-12:

100.

3. The photonic crystal hydrogel-based thermochromic smart window material according to claim 1, characterized in that: The temperature-sensitive monomer is one or more of N-isopropyl acrylamide, N-tert-butyl acrylamide, N,N-diethyl acrylamide, N-propyl acrylamide, N,N-dimethyl acrylamide, dimethylaminopropyl acrylamide, and ethoxyethoxyethyl acrylate.

4. The photonic crystal hydrogel-based thermochromic smart window material according to claim 1, characterized in that: The modified cellulose is prepared by esterification reaction or etherification reaction of cellulose.

5. The photonic crystal hydrogel-based thermochromic smart window material according to claim 4, characterized in that: The modified cellulose is one or more of methyl cellulose, carboxymethyl cellulose, hydroxypropyl cellulose, hydroxypropyl methyl cellulose and cellulose nanofiber.

6. The photonic crystal hydrogel-based thermochromic smart window material according to claim 1, characterized in that: The cross-linking agent is one or more of N,N'-methylenebisacrylamide, polyethylene glycol diacrylate, and allyl methacrylate; the initiator is one or more of ammonium persulfate, potassium persulfate, and sodium persulfate; the transparent conductive oxide nanoparticles are one or more of indium tin oxide, antimony tin oxide, and zinc aluminum oxide; the colloidal particle dispersion is prepared by dispersing colloidal particle powder in deionized water; the colloidal particles are polystyrene microspheres, polymethyl methacrylate microspheres, SiO2 microspheres, TiO2 microspheres, or ZnO2 microspheres.

7. The photonic crystal hydrogel-based thermochromic smart window material according to claim 6, characterized in that: The mass fraction of the colloidal particles in the dispersion is 20-30 wt %; the particle size of the colloidal particles is 160-280 nm.

8. The photonic crystal hydrogel-based thermochromic smart window material according to claim 1, characterized in that: The curing temperature is 4-15 °C, and the curing time is 12-24 h; the stirring under ice bath conditions is performed until completely dissolved, the initiator is added and stirred until dissolved, and the stirring involved in the addition of N, N, N', N'-tetramethylethylenediamine is magnetic stirring, and the stirring speed is 500-1000 rpm; the stirring time for adding N, N, N', N'-tetramethylethylenediamine is 30-60 s; the ultrasonic dispersion time is 60-120 min; the centrifugal speed is 4000-8000 rpm, and the centrifugal time is 40-60 min; the carrier is glass.

9. The method for preparing the photonic crystal hydrogel-based thermochromic smart window material according to any one of claims 1 to 8, characterized in that The steps include: A method for preparing a photonic crystal hydrogel-based thermochromic smart window material, characterized by comprising the following steps: (1) Centrifuging the colloidal particle dispersion until the colloidal particles are pre-assembled on the wall of the centrifuge tube to form hierarchical light spots of different colors, thereby obtaining colloidal crystals; (2) adding transparent conductive oxide nanoparticles to the colloidal crystals in step (1), and dispersing them by ultrasonication to obtain modified colloidal crystals; (3) The modified colloidal crystals are self-assembled on the carrier by scraping or spin coating to form a periodically ordered three-dimensional photonic crystal structure; (4) adding the thermosensitive monomer, modified cellulose and crosslinking agent into deionized water, and stirring in an ice bath until the monomer is completely dissolved after ultrasonic dispersion, adding the initiator and stirring until dissolved, and then adding the catalyst N,N,N',N'-tetramethylethylenediamine and stirring evenly to obtain a thermosensitive hydrogel prepolymer solution; (5) Filling the thermosensitive hydrogel prepolymer solution of step (4) with the three-dimensional photonic crystal structure self-assembled on the carrier of step (3) and then curing it to obtain a photonic crystal hydrogel-based thermochromic smart window material.

10. Use of the photonic crystal hydrogel-based thermochromic smart window material according to any one of claims 1 to 8 in preparing smart windows.

Citation Information

Patent Citations

  • Thermochromic window

    CN104129121A

  • A thermosensitive gel material for smart windows and its preparation method

    CN114573756B

  • Preparation methods of ion-hydrogel electrolytes, smart window devices and their fabrication methods

    CN116284850B

  • Near-infrared detection colorimetric sensor as well as preparation method and application thereof

    CN111879711A

  • Photo-thermal dual-response intelligent window and preparation method thereof

    CN113667142A

Cited By

  • Preparation method of temperature-sensitive color-changing packaging film

    CN121271001A

  • Phase change magnetic fluid, preparation method and application thereof, and method for absorbing and desorbing carbon dioxide

    CN122537913A